2009
DOI: 10.3892/or_00000542
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein (HBx) induces G2/M arrest and apoptosis through sustained activation of cyclin B1-CDK1 kinase

Abstract: Abstract. Hepatitis B virus X protein (HBx) is a multifunctional regulatory protein that is known to be involved in viral proliferation, transcriptional activation and cell growth control. However, the actual role of HBx in cell growth control remains controversial. In this study, the impact of HBx on cell growth in vitro and in vivo was further investigated. HBx was able to inhibit the growth of hepatocellular carcinoma (HCC) cells and induce G2/M arrest in vitro. Moreover, unlike many other G2/M arrest mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that CDK1/CCNB1 inhibits the p53 signaling pathway and regulate the development of HCC [ 8 ]. An in vitro study demonstrated that HBV X protein (HBx) induces G2/M phase arrest and apoptosis through continuous activation of CDK1/CCNB1 kinase [ 31 ]. Other studies reported that both CCNB1 and CDK1 are overexpressed in HBV-related HCC tissues and are associated with poor survival [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CDK1/CCNB1 inhibits the p53 signaling pathway and regulate the development of HCC [ 8 ]. An in vitro study demonstrated that HBV X protein (HBx) induces G2/M phase arrest and apoptosis through continuous activation of CDK1/CCNB1 kinase [ 31 ]. Other studies reported that both CCNB1 and CDK1 are overexpressed in HBV-related HCC tissues and are associated with poor survival [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…UGT1A4, CYP2A6, CSF2, INRS, GSTM1, and BMP6 had the lowest relevance score of 20.08, 20.03, 20.47, 20.02, 20.0, and 20.02, respectively. The list of genes/protein molecules regulated by the HBV and each chemical-induced hepatitis which is obtained from a peer review of the literature (along with references [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , ...…”
Section: Resultsmentioning
confidence: 99%
“…G2/mitotic-specific cyclin-B1 (CCNB1) was a major activator of CDK1 [ 31 ]. Studies showed that HBV activated CCNB1-CDK1 kinase in HCC cells in vitro [ 32 ]. CCNB1 and CDK1 were upregulated in HCC tissues of HBV-positive patients [ 33 ], and overexpression of CCNB1 and CDK1 was associated with poor prognosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%